2014
DOI: 10.1111/ped.12281
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidosis type VI in Russia, Kazakhstan, and Central and Eastern Europe

Abstract: The observed high p.R152W carrier frequency in the Lithuanian population may indicate a possible founder effect in this region. The high prevalence of this mutation observed in the whole series, as well as the Slavic origin of the majority of patients homozygous for this mutation, suggest that p.R152W may be of Slavic, not Lithuanian origin. Resettlement of the Polish population after World War II resulted in dilution of the prevalence of carriers in Poland and a very low MPS VI incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
2
18
0
2
Order By: Relevance
“…Both the low and high uGAG groups showed stabilization of endurance (6MWT, 3MSCT) and pulmonary function (FEV 1 , FVC, and MVV) after 6 to 8 years follow‐up. When interpreting these results, one should consider the natural history of MPS VI, associated with a gradual deterioration of clinical manifestations with aging, and resulting in premature mortality . The long‐term improvements in endurance and pulmonary function seen in the present study suggest that ERT stabilizes MPS VI disease progression in the long‐term.…”
Section: Discussionmentioning
confidence: 52%
“…Both the low and high uGAG groups showed stabilization of endurance (6MWT, 3MSCT) and pulmonary function (FEV 1 , FVC, and MVV) after 6 to 8 years follow‐up. When interpreting these results, one should consider the natural history of MPS VI, associated with a gradual deterioration of clinical manifestations with aging, and resulting in premature mortality . The long‐term improvements in endurance and pulmonary function seen in the present study suggest that ERT stabilizes MPS VI disease progression in the long‐term.…”
Section: Discussionmentioning
confidence: 52%
“…The MPS VI incidence values for Poland were the lowest of all the studies previously published so far. Interestingly, in our previous study, we found high incidence rates for MPS VI in countries neighboring with Poland (Jurecka et al 2014 ). In fact, they were the highest in Europe among those reported so far.…”
Section: Discussionmentioning
confidence: 72%
“…Jurecka et al have reported MPS VI cases between 1983 and 2011 in Kazakhstan and Russia and compared with central and eastern European countries [133]. A high incidence of the p.R152W mutation was observed both in the whole series (42%) as well as in Russian patients (43%).…”
Section: Discussionmentioning
confidence: 99%